(untitled) (Revista Direitos Humanos e Democracia, 2026)
We investigated some of the main regulations that guide Human Rights Education in our country, occasionally turning to a gender perspective with a focus on preventing domestic violence against women. Methodologically, a bibliographical research was carried out, complemented by documentary research, with analysis of books, articles, videos, legal documents, Brazilian political documents and other materials. We aim to build an expanded discursive corpus and, at the same time, delimit the current normative scenario on the topic. The results demonstrate that, although the Brazilian legal framework incorporates principles of gender equality and respect for human rights, its application remains limited. It is observed that a focus on gender and the prevention of violence against women has remained sporadic and fragmented, not being transversally materialized in curricula and lacking consistent support for qualified teacher training. We conclude that the effective implementation of Human Rights Education with a gender perspective demands integrated public policies, ongoing training for educators, and the systematic inclusion of the topic in pedagogical practices in order to promote a school culture of equality and non-violence.